2019
DOI: 10.1002/ecy.2935
|View full text |Cite
|
Sign up to set email alerts
|

Browsing and fire decreases dominance of a resprouting shrub in woody encroached grassland

Abstract: North American grasslands have experienced increased relative abundance of shrubs and trees over the last 150 yr. Alterations in herbivore composition, abundance, and grazing pressure along with changes in fire frequency are drivers that can regulate the transition from grassland to shrubland or woodland (a process known as woody encroachment). Historically, North American grasslands had a suite of large herbivores that grazed and/or browsed (i.e., bison, elk, pronghorn, deer), as well as frequent and intense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 71 publications
0
43
1
Order By: Relevance
“…However, I found no difference in nonstructural carbohydrates between burned and control trees. Contrastingly, a threefold decrease in total nonstructural carbohydrates (sugars and starches) was found in a resprouting rangeexpanding woody shrub Cornus drummondii after browsing and a prescribed fire in Kansas [3]. In another study, root starch was found to be a key nutrient that limits resprouting ability after fires in two savanna shrubs, Miconia albicans and Clidemia sericea [150].…”
Section: Optimal Partitioning Theorymentioning
confidence: 91%
See 2 more Smart Citations
“…However, I found no difference in nonstructural carbohydrates between burned and control trees. Contrastingly, a threefold decrease in total nonstructural carbohydrates (sugars and starches) was found in a resprouting rangeexpanding woody shrub Cornus drummondii after browsing and a prescribed fire in Kansas [3]. In another study, root starch was found to be a key nutrient that limits resprouting ability after fires in two savanna shrubs, Miconia albicans and Clidemia sericea [150].…”
Section: Optimal Partitioning Theorymentioning
confidence: 91%
“…Native species are capable of spreading rapidly into new habitats and niches, and act similarly to invasive species, usually in response to a disturbance of that habitat [1][2][3]. However, invasive species were far more likely than native species to respond to disturbances [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent shifts in shrub cover were only found in our pixel‐by‐pixel analysis. Resprouting shrub species are generally unresponsive to low‐intensity fires that occur in the absence of browsers in local field‐based studies (O'Connor et al, 2020; Ratajczak et al, 2014), while high‐intensity fire can drive a decrease in shrub cover (Ansley & Jacoby, 1998; Twidwell et al, 2016). Our results likely reflect some of this heterogeneity in fire intensity created by wildfire.…”
Section: Discussionmentioning
confidence: 99%
“…The sparse U. pumila trees on the temperate savanna-like ecosystem have ecological significance because they provide sand stabilization and also resting places for livestock [19]. In recent years, due to various changing conditions, such as climate change and land use change in the course of economic development [20][21][22], there has been severe damage to the U. pumila-dominated temperate savanna-like ecosystem. This damage has led to an increase in the number of shrubs and the densification of woody plant cover as well as outcomes such as decreasing temperate savanna-like ecosystem area, the loss of structural integrity, poor population regeneration, and changing spatial patterns [23,24].…”
Section: Introductionmentioning
confidence: 99%